KEMAMPUAN PENGUASAAN MAJAS PERTENTANGAN SISWA KELAS XII SMK KESEHATAN SAHATA KOTA PEMATANGSIANTAR - Dedi Zulkarnaen Pulungan (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2015)
Figure of speech CONFLICT CONTROL CAPABILITIES HEALTHCLASS XII SMK SAHATA CITY PEMATANGSIANTAR LESSONS YEAR 2014-2015 DEDI ZULKARNAIN Pulungan NIM : 8136192007 FIELD STATEUNIVERSITY GRADUATE INDONESIAN ABSTRACT The research wasconducted in SMK SAHATA Health Academic Year 2014-2015 100 City RoadMelanthon siregar Pematangsiatar.dengan penelitain Methods Descriptive . Thisstudy aimed to describe the ability of opposition figure of speech in a sentencemastery class XII student of SMK HEALTH SAHATA Pematangsiantar 2014-2015academic year of calculation of the percentage figure of speech known masteryability opposition in class XII student sentence quite able to value - average (mean ) 70.33 . Students were categorized memproleh value (A) there is as muchas 33.33 % gain value (B) there is as much as 26.67 % , gain value (C) there is asmuch as 20 % , memproleh value (D) there are as many as 20 % and categoryvalue (E) there as much as 0 % .From the results of the analysis of data and thenumber of students who meet the criteria of completeness of the results of theability to master figure of speech in a sentence contradictions exist in bothcategories with the amount of 80 %.